A 1, 8-naphthalimide-based chemosensor for dual-mode sensing: colorimetric and fluorometric detection of multiple analytes. Issue 87 (5th September 2016) - La, Yeo-Kyung; Hong, Jong-Ah; Jeong, Yujin; Lee, Jiyoun
Abstract : A dual-mode sensor 1 demonstrated highly specific and sensitive signal changes to multiple analytes based on two distinct mechanisms. Abstract : We designed a 1, 8-naphthalimide-based chemosensor for dual-mode sensing of multiple analytes. Sensor 1 contains a hydrazone linker with a quinoline group that can generate CN − and F − -specific color changes while exhibiting Hg 2+ -specific fluorescence enhancement. Sensor 1 demonstrated highly specific and sensitive signal changes upon binding to these ions with detection limits in the submicromolar range. We believe that sensor 1 responds to anions and cations by two distinct mechanisms, thus enabling dual-mode detection of multiple analytes.